The Effect Of Roa And Roe On The Profit Growth Of Government Banks With Credit Growth As An Intervening Variable - Mei Hotma Mariati Munte; Jadongan Sijabat (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
Company performance information reflected in profit information in the comprehensive income statement is important information seen by investors in making decisions regarding investment and credit, and also information for evaluating management's performance in managing the company. The company's good profit growth reflects that the company's performance is also good. In other words, profit is a measure of a company's performance, so the higher the profit it achieves, the better its performance. This study aims to test and analyze the effect of ROA on profit growth, the effect of ROA on profit growth with credit growth as an intervening variable, the effect of ROE on profit growth, ROE on profit growth with credit growth as an intervening variable, the influence of ROA and ROE on profit growth and the effect of ROA and ROE on profit growth with credit growth as an intervening variable. Based on the test results, the value of the ROA coefficient is -12.031, with a significance level of 0.153. So it can be stated that the hypothesis (Ha1) states that the ROA ratio does not influence credit growth in government banks is acceptable. The results of hypothesis testing (Ha2) in which the value of the ROA coefficient is -3.415 with a significance level of 0.067 can then be stated that the hypothesis (Ha2) stating that the ROA ratio does not affect profit growth with credit growth as an intervening variable in government banks is acceptable. The results of testing the ratio of ROE to profit growth show that the ratio of ROE with a coefficient value of 1.854 with a significance level of 0.095 has a positive but insignificant effect on profit growth. So it can be stated that the hypothesis (H03), which states that the ROE Ratio affects profit growth in government banks, is acceptable. The results of testing the ratio of ROE to profit growth with credit growth as an intervening variable showed that the ROE ratio had a positive effect with a coefficient value of 0.487 with a significance level of 0.045. So it can be stated that the hypothesis (H04), which states that the ROE ratio affects profit growth with credit growth as an intervening variable in government banks, is acceptable. Furthermore, the test results on the effect of credit growth on profit growth showed that the value of the credit growth coefficient of 1.093 and significant at 0.182 was a positive but insignificant effect. Thus the hypothesis (H05) of profit growth influencing the credit growth of government banks is acceptable.